2014
DOI: 10.5901/mjss.2014.v5n14p531
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fighting and Social Correlates among In-School Adolescents in the Caribbean

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
9
11
2
Order By: Relevance
“…This study found no association between socioeconomic status and physical fights. Socioeconomic status has been associated with physical fighting [10,33,42], though no association was found in a study in Ghana [9], in the Caribbean [3], and among males in Canada [27]. The studies in the Caribbean, Ghana, and the current study used hunger as a measure of socioeconomic status while other studies have used self-reported affluence, family affluent scale, or average household income as a unit of measurement.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This study found no association between socioeconomic status and physical fights. Socioeconomic status has been associated with physical fighting [10,33,42], though no association was found in a study in Ghana [9], in the Caribbean [3], and among males in Canada [27]. The studies in the Caribbean, Ghana, and the current study used hunger as a measure of socioeconomic status while other studies have used self-reported affluence, family affluent scale, or average household income as a unit of measurement.…”
Section: Discussioncontrasting
confidence: 53%
“…Supportive parents were found to be protective of physical fights as observed in other studies in Ghana, Namibia, and Chile [9,28,38] though not in studies from the Caribbean and Malaysia were no association was noted [3,22]. On the other hand, supportive parents were found to have an increased risk among males but protective among females in Qatar [25].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In bivariate analysis, psychological distress was also found to increase the odds for physical fighting, as found in previous studies (12,(15)(16)(17). Various researchers (6,(8)(9)(10) indicated that we may have here a clustering of unhealthy behaviors, which could mean that interventions should also address multiple risk behaviors in adolescents.…”
Section: Discussionsupporting
confidence: 76%
“…Factors associated with physical fighting in adoles-cents can be grouped into sociodemographic factors, risk behaviors, including psychological distress, and lack of protective social-familial factors (8). Sociodemographic factors may include, male gender (3,9,10), decreased with age (3,11), low economic status (3,12), living in lower income countries (2).…”
Section: Introductionmentioning
confidence: 99%